Boundedness of Marcinkiewicz Integrals and Their Commutators on Generalized Weighted Morrey Spaces. (15th January 2015) - Cui, Runqing; Li, Zhang
Abstract : We will study the boundedness of Marcinkiewicz integrals with rough kernel on the generalized weighted Morrey spaces. We will also prove that the commutator operators formed by aB M O R n function and Marcinkiewicz integrals are also bounded on the generalized weighted Morrey spaces.